1)
x² - 6x - 3 = 0
x² - 6x = 3
x² - 6x + 9 = 3 + 9
(x - 3)² = 12
|x - 3| = √12 = 2√3
x₁ = 3 + 2√3 x₂ = 3 - 2√3
x² - 6x = 3
x² - 6x + 9 = 3 + 9
(x - 3)² = 12
|x - 3| = √12 = 2√3
x₁ = 3 + 2√3 x₂ = 3 - 2√3
2) 2w²-8 = 0
2w² = 8
w² = 8/2
w² = 4
w = ± √4
w₁ = -2 w₂ = 2
2w² = 8
w² = 8/2
w² = 4
w = ± √4
w₁ = -2 w₂ = 2
3)
√x-3 - 1/2 = x
√x-3 = x + 1/2
(√x-3)² = (x + 1/2)²
x - 3 = x² + x + 1/4
x² + 1/4 + 3 = 0
x² + 13/4 = 0
x² = -13/4
x = ± √-13/4
x₁ = -√13/2 x₂ = √13/2
√x-3 = x + 1/2
(√x-3)² = (x + 1/2)²
x - 3 = x² + x + 1/4
x² + 1/4 + 3 = 0
x² + 13/4 = 0
x² = -13/4
x = ± √-13/4
x₁ = -√13/2 x₂ = √13/2
K2- 4 (36) =0 k2 =144
K= ± sqrt 144
k1 = 12
k2= -12
X= 4 ± sqrt 16-16/2
= 4/2 =2
No hay comentarios:
Publicar un comentario